Sex biology contributions to vulnerability to Alzheimer's disease: A think tank convened by the Women's Alzheimer's Research Initiative. Issue 11 (26th September 2016) - Snyder, Heather M.; Asthana, Sanjay; Bain, Lisa; Brinton, Roberta; Craft, Suzanne; Dubal, Dena B.; Espeland, Mark A.; Gatz, Margaret; Mielke, Michelle M.; Raber, Jacob; Rapp, Peter R.; Yaffe, Kristine; et al.
Abstract: More than 5 million Americans are living with Alzheimer's disease (AD) today, and nearly two‐thirds of Americans with AD are women. This sex difference may be due to the higher longevity women generally experience; however, increasing evidence suggests that longevity alone is not a sufficient explanation and there may be other factors at play. The Alzheimer's Association convened an expert think tank to focus on the state of the science and level of evidence around gender and biological sex differences for AD, including the knowledge gaps and areas of science that need to be more fully addressed. This article summarizes the think tank discussion, moving forward a research agenda and funding program to better understand the biological underpinnings of sex‐ and gender‐related disparities of risk for AD.